The significance of amniotic fluid immunological analysis for the prediction of intrauterine infection - G. Balciuniene; L. Jakubauskiene; G.S. Drasutiene; A. Meskauskiene; D. Ramasauskaite (IMR Press, 2020)
Intrauterine infection, a dangerous condition for a pregnant woman and her fetus, increases the risk of neonatal death and the incidence of severe diseases like cerebral palsy, chronic lung illnesses and psychomotor disorders. Better prediction of intrauterine infection would support the choice of an appropriate treatment plan during pregnancy and suitable healthcare for the mother and newborn after birth. Herein, we review the immunological analysis of amniotic fluid for prediction of intrauterine infection and survey advances in the field that are bringing us closer to clinical implementation.